Problem-based Learning and Creativity - Tan, Oon Seng 320511; Gale Group (Online service) 651863 (Singapore : Cengage Learning Asia Pte Ltd., 2009)
Problem-based learning (PBL) is an educational innovation for greater diversity and engagement in learning. PBL diversifies learning by catering for interdisciplinary knowledge application and multiple perspectives in problem solving. It also enhances engagement through more independent learning, peer learning and teamwork in problem solving with possibilities of future learning technologies. This collection on PBL and creativity provides another quantum leap by linking the quest for novelty, creativity and innovation with PBL. One of the key features of the PBL environment is immersion in a problem context.